Pengaruh Brand Trust Memediasi Electronic Word of Mouth terhadap Purchase Intention pada Brand Fashion Hamata Studios - I Putu Bintang Pramesta Ardhyan; Tjokorda Gde Raka Sukawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The rapid growth of e-commerce and social commerce in Indonesia has shifted consumer behavior in seeking information prior to making purchase decisions, particularly through electronic word of mouth (e-WOM). This phenomenon poses a challenge for local fashion brands such as Hamata Studios, which has relatively low digital visibility despite having favorable product ratings. This study aims to analyze the effect of e-WOM on purchase intention with brand trust as a mediating variable based on the Stimulus-Organism-Response (S-O-R) theory. This research employs a quantitative approach with an associative research design. Data were collected through questionnaires distributed to respondents who are familiar with or have interacted with Hamata Studios, using a non-probability sampling technique with a purposive sampling method. Data analysis techniques include descriptive and inferential statistical analysis using path analysis, as well as mediation testing using the Sobel test and Variance Accounted For (VAF). The results indicate that e-WOM has a positive and significant effect on both purchase intention and brand trust. Furthermore, brand trust has a positive and significant effect on purchase intention. Mediation testing reveals that brand trust significantly mediates the relationship between e-WOM and purchase intention. In conclusion, positive e-WOM can enhance brand trust, which in turn increases consumers’ purchase intention.